Non-Muslim perception of Islam and Muslims based on depiction of Islam in media reports, Malaysia - Parvin, Ali (2015)
Various studies have proven the leverage of the media exposure in exerting their power on the mindset of the audiences. Therefore, this study tempted to investigate the exposure of media reports on Islam among Malaysian non-Muslims to understand if exposing to the media’s reports paves the way for changes in the perception. For further exploring the topic, the main objectives of the study are firstly to identify perception of non-Muslim Malaysians towards information concerning Islam and Muslims in the media. Then, describing the non-Muslims’ perception in Malaysia towards media reliability followed by determining the perception of non-Muslims in Malaysia towards understanding Islam and Muslims based on media reports. As the nature of conducting research is truly based on the problem statement, this study has found media contents are misleading and unreliable. These problems have the capacity of destabilizing by generating negative depictions on the perceptions. Significantly, in a multicultural country like Malaysia where various races are living together in harmony and peace, small portion of negative beliefs or reports on any religions or sect could jeopardizes the peace process in the nation. Thus, this study has chosen a sample size of 380 non-Muslim Malaysians over the population of 40,070 people within the Seri Kembangan district. There are vast numbers of Chinese and considerable number of Indians in the area who are expose to the mass media and news reports. Contrary, an advantage to the subjects of this study is that multiracial populations reside in the area. However, to fulfill the objectives of this study a quantitative method was adopted to collect the primary data. This research study is based on non-probability sampling where all data was gathered through self-administrative questionnaire by using convenient sampling. Series of correlation tests were done to understand the relationship between information about Islam and Muslims by media as well as media reliability towards formation of the non-Muslims perception. The major results concludes that mass media in general are all pervasive in their reports but not particularly pervasive. This statement summarizes most of the significant in currently accepted perceived facts about mass media in Malaysia. Regardless of media’s exposure, non-Muslims in Malaysia hold positive perceptions towards their fellow Muslims. Likewise, framing and agenda-setting of the media does not have any penetrations on the peacefulness of non-Muslims’ mindset. As non-Muslims in Malaysia are well aware of the media hegemony, one’s ideology could not be simply breached by negative reports. Significantly, non-Muslims respect Islam as the official religion of people in Malaysia.